FAKTOR-FAKTOR DOMINAN YANG MEMPENGARUHI LAMA MENCARI PEKERJAAN DI SEMARANG MENGGUNAKAN ANALISIS REGRESI COX - Anissatush Sholiha; Rochdi Wasono; Tiani Wahyu Utami (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Discussion on the issue of unemployment is always associated with variousfactors that affect the length of time a person needs to get a job.One commonmethod used to determine these factors is to conduct survival analysis, amongwhich commonly used is Cox Proportional Hazard Regression.The purpose ofthis study was to identify the various factors of the time needed to be employeda university fresh graduate. The variables used consist of time to be employedas the dependent variable, while the independent variables are the educationalbackground, family income, job vacancies and the work aspiration. Coxregression can be the most appropriate method because the function andpurpose of this analysis is to predict exactly what factors make a person take acertain time to get his current job. The survival function and hazard functionpresent in the cox regression method allow the estimated time required by aperson until the person experiences an event (in which case the event is gettinga job). The results obtained from the analysis of each of these variables provedto have a significant effect on the length of time seeking employment of privateworkers in the city of Semarang.Keywords: Unemployed Length, Proportional Hazard Cox Regression, Survival.